Characteristics of Organizational Culture Based on Local Wisdom - Junaris, Imam; Wahid, Abd Hamid; Atiqoh, Dewi; Rohmatun, Rohmatun (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to understand the characteristics of organizational culture based on local wisdom in an early childhood education institution in Probolinggo Regency, East Java. The research method used is a qualitative case study type. In order to get an overview of the characteristics of the local wisdom-based organizational culture, the researchers conducted direct observations and documented activities at the institution. Interviews were conducted with principals, teachers, and guardians of students. The results showed that the characteristics of local wisdom-based organizational culture developed in schools include; child-friendly school-based women's leadership, the dual role of a teacher, strong work ethic, and religion. This study implies that developing organizational culture characteristics based on local wisdom can give complete trust to the community in these organizational institutions.